Effects of fetal haemoglobin on systemic oxygenation in preterm infants and the development of retinopathy of prematurity PacIFiHER Report No. 2. Issue 3 (7th October 2021) - Jiramongkolchai, Kim; Repka, Michael X; Tian, Jing; Aucott, Sue W; Shepard, Jennifer; Collins, Megan; Clemens, Julia; Feller, Mia; Burd, Irina; Roizenblatt, Marina; Smith, Kerry; Arevalo, J Fernando; et al.
Abstract : Background/aims: Fetal haemoglobin (HbF) has an oxyhaemoglobin dissociation curve that may affect systemic oxygenation and the development of retinopathy of prematurity (ROP). The study aim is to characterise the effects of HbF levels on systemic oxygenation and ROP development. Methods: Prospective study conducted from 1 September 2017 through 31 December 2018 at the Johns Hopkins NICU. Preterm infants with HbF measured at birth, 31, 34 and 37 weeks post-menstrual age (PMA), complete blood gas and SpO2 recorded up to 42 weeks PMA, and at least one ROP exam were included. Results: Sixty-four preterm infants were enrolled. Higher HbF was associated with significantly higher SpO2, lower PCO2, lower FiO2 from birth to 31 weeks PMA and 31 to 34 weeks PMA (rs =0.51, rs =−0.62 and rs =−0.63; p<0.0001 and rs =0.71, rs =−0.58 and rs =−0.79; p<0.0001, respectively). To maintain oxygen saturation goals set by the neonatal intensive care unit, higher median FiO2 was required for HbF in the lowest tercile from birth compared with HbF in the highest tercile to 31 weeks and 31 to 34 weeks PMA; FiO2 =35 (21–100) versus 21 (21–30) p<0.006 and FiO2 =30 (28–100) versus 21 (21–30) p<0.001, respectively. Preterm infants with ROP had poorer indices of systemic oxygenation, as measured by median levels of SpO2 and PCO2, and lower levels of HbF (p<0.039 and p<0.0001, respectively) up to 34 weeks PMA. Conclusion: Low HbF levels correlated with poor oxygenation indices and increased risk for ROP. O2 saturation goals to prevent ROP may need to incorporate relative amount of HbF.